Knowledge gaps in fitness-for-service assessment procedures; summary of the 2nd 'mind the gap' workshop. (April 2023) - Hadley, Isabel; Zerbst, Uwe; Coules, Harry; James, Peter; Sharples, John; Bhat, Shivaprasad Shridhara; Larrosa, Nicolas
Abstract: In 2015, the University of Manchester hosted a workshop ('Mind the Gap') aimed at identifying gaps in a number of structural integrity fitness-for-service procedures, including R5, R6, BS 7910 and API/ASME. The findings were subsequently summarised in a journal paper and shared with the relevant stakeholders. A second workshop, this time hosted by the University of Bristol in 2017, was intended to build on the findings of the earlier event, identifying which gaps had been filled, which remain and whether new ones have been identified in the meantime. 'Mind the Gap 2' was wide-ranging, including consideration of failure by fracture, fatigue crack growth, hightemperature creep and environmentally assisted crack growth, along with the use of innovative techniques to follow the progress of crack growth from the atomic to the macroscopic scale. A summary of the whole event is thus outside the scope of a single paper, so here we concentrate mainly on advances in fracture assessment, on the interface between inspection and ECA, and on how developments are being incorporated into structural integrity procedures. There is a particular emphasis on the energy transition in the UK, where the planned energy mix will include both nuclear power and offshore wind. Highlights: Interface between non-destructive testing and structural integrity assessment. Inspection and assessment of non-sharp defects. Codes and standards for future reactor systems. Enhancements to fracture assessment procedures.